Toward Developing a Preventive MERS-CoV Vaccine—Report from a Workshop Organized by the Saudi Arabia Ministry of Health and the International Vaccine Institute, Riyadh, Saudi Arabia, November 14–15, 2015 - Jean-Louis Excler; Christopher J. Delvecchio; Ryan E. Wiley; Marni Williams; In-Kyu Yoon; Kayvon Modjarrad; Mohamed Boujelal; Vasee S. Moorthy; Ahmad Salah Hersi; Jerome H. Kim (Emerging Infectious Diseases, 2016)
Middle East respiratory syndrome (MERS) remains a serious international public health threat. With the goal of accelerating the development of countermeasures against MERS coronavirus (MERS-CoV), funding agencies, nongovernmental organizations, and researchers across the world assembled in Riyadh, Saudi Arabia, on November 14–15, 2015, to discuss vaccine development challenges. The meeting was spearheaded by the Saudi Ministry of Health and co-organized by the International Vaccine Institute, South Korea. Accelerating the development of a preventive vaccine requires a better understanding of MERS epidemiology, transmission, and pathogenesis in humans and animals. A combination of rodent and nonhuman primate models should be considered in evaluating and developing preventive and therapeutic vaccine candidates. Dromedary camels should be considered for the development of veterinary vaccines. Several vaccine technology platforms targeting the MERS-CoV spike protein were discussed. Mechanisms to maximize investment, provide robust data, and affect public health are urgently needed.